Cytotoxic screening of endophytic fungi associated with Catharanthus roseus - CATERINA SISKADEWI LAY; IKRA AGUSTINA; PUJI ASTUTI; TRIANA HERTIANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lay CS, Agustina I, Astuti P, Hertiani T. 2023. Cytotoxic screening of endophytic fungi associated with Catharanthus roseus. Biodiversitas 24: 2716-2722. Despite the advancements in cancer therapy, there is still a need for new anticancer agents. Due to the tremendous range of chemical compounds that endophytic fungi create, they have become a crucial component of the current drug development process. The aim of this study was to evaluate the cytotoxic potential of endophytic fungi associated with Catharanthus roseus (L.) G.Don collected from Yogyakarta, Indonesia. All fungal EtOAc extracts were tested against three human cancer cell lines, HeLa, T47D, MCF-7, and Vero cell lines. The potential fungal isolate was identified using molecular techniques. The results showed that a total of seven endophytic fungi were obtained from the different parts of C. roseus. Only one fungus (SCR 3) showed the best cytotoxic activitiy towards all three cell lines used, especially the MCF-7 cell line (IC50 130.90 ?g/mL, Selectivity Index=11.42). The findings of using LC-HRMS also revealed several exciting compounds such as genistein and D-(-)-Mannitol. The results showed that EtOAc extract of SCR 3 (Aspergillus sp.) induced apoptosis but did not affect the cell cycle. This study suggests that EtOAc extract of SCR 3 may be a potential source of secondary metabolites that can function as a new source of anticancer agents.